Assessment of the ecological footprint of smart cities through sustainable development indicators - Nikolov, Nikolay (Annual of Natural Sciences Department, 2025)
The concept of a "smart city" should not be associated solely with a "digital city". A city can be classified as a smart city if economic activities, mobility, environmental resources, relationships between people, housing policy and the way in which technological innovations are implemented are intelligently managed. The aim of the study is to establish the ecological footprint of smart cities through sustainable development indicators. The results show that Carbon dioxide (CO₂) emissions are associated with emissions from industrial processes, as well as from the burning of fossil fuels. The conclusion that can be reached is that although Sofia has lower CO₂ emissions per capita than Amsterdam in 2024, the trend is worrying, as emissions are increasing on an annual basis, while for Amsterdam and Vienna they are decreasing. For Sofia, the green area per capita is found to be 9 square meters per person. A comparison of the three cities shows that Vienna is the city with the largest amount of green space per capita. The capital of Austria is distinguished by over 55% green space of its total area, which means that each resident has an average of 120 square meters of green space, including parks, gardens, and other green areas. Annual average PM concentrations in Sofia are significantly higher than those recommended by the WHO. The data analysis shows that among the three cities studied, the average annual PM10 level is highest in Sofia, followed by Vienna. The indicator in Amsterdam has a significantly lower value.